2018
DOI: 10.1519/jsc.0000000000001817
|View full text |Cite
|
Sign up to set email alerts
|

Is Vertical Jump Height an Indicator of Athletes' Power Output in Different Sport Modalities?

Abstract: Kons, RL, Ache-Dias, J, Detanico, D, Barth, J, and Dal Pupo, J. Is vertical jump height an indicator of athletes' power output in different sports modalities? J Strength Cond Res 32(3): 708-715, 2018-This study aimed to identify whether the ratio standard is adequate for the scaling of peak power output (PPO) for body mass (BM) in athletes of different sports and to verify classification agreement for athletes involved in different sports using PPO scaled for BM and jump height (JH). One hundred and twenty-fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…However, allometric scaling is a correction method that is also based on assumptions, and may not apply correctly in heterogeneous populations, and/or in the case of very specific body composition and especially skeletal muscle mass as developed through years of specific training in elite athletes. Kons et al recently showed that the improvement of correlations between jump height and Pmax through allometric scaling was highly sport-specific [33]. Interestingly, Fig.…”
Section: 2mentioning
confidence: 88%
See 2 more Smart Citations
“…However, allometric scaling is a correction method that is also based on assumptions, and may not apply correctly in heterogeneous populations, and/or in the case of very specific body composition and especially skeletal muscle mass as developed through years of specific training in elite athletes. Kons et al recently showed that the improvement of correlations between jump height and Pmax through allometric scaling was highly sport-specific [33]. Interestingly, Fig.…”
Section: 2mentioning
confidence: 88%
“…1) include: variable hPO values among athletes, heterogeneous individual Fv profiles and optimal profiles, and in turn optimal load that differs from body mass for some athletes (which was the case for most rugby players). Finally, two recent studies show that athlete's absolute lower limb power output capability could not be appropriately categorized or estimated, in most sports, from jump height measurements [32,33]. Among the practical solutions to solve this issue, the current authors propose to use estimations based on regressions, and allometric scaling of raw, absolute power values.…”
Section: Fig 2 Correlations (Pearson's R) Between Countermovement Jmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the correction of BM variations may be advisable if a judo trainer, coach, or athlete is interested in a straightforward comparison between athletes with different BMs. In this regard, a traditional mathematical approach, such as the socalled allometric exponent adjustment, may be helpful [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Abad et al [12] reported that the 10 km running performance was better predicted through a model combining peak treadmill running velocity and running economic data allometrically adjusted. Actually, a recent study suggested that the allometric model seems to be a more straightforward strategy for performance analysis in combat sports [11]. In this sense, one may hypothesize that allometric exponents further correct BM variations-derived distortions in SJTF performance outcomes.…”
Section: Introductionmentioning
confidence: 99%